Invasive dermatophyte infection with Trichophyton interdigitale is associated with prurigo‐induced pseudoperforation and a signal transducer and activator of transcription 3 mutation. (1st September 2018) - Simpson, J.K.; Fröbel, P.; Seneviratne, S.L.; Brown, M.; Lowe, D.M.; Grimbacher, B.; Fliegauf, M.; Fearfield, L.
Summary: Invasive dermatophyte infection, with extension beyond the dermis, in immunocompetent hosts is exceptionally rare. Dermatophytes are keratinophilic and are usually confined to the stratum corneum, hair and nails. Susceptibility to dermatophyte infections is incompletely understood, but inherited mutations in key signalling pathways of the innate immune system have been identified. We report the first case of an invasive dermatophyte infection associated with abrupt onset of a prurigo‐induced pseudoperforation and a loss‐of‐function mutation in signal transducer and activator of transcription 3 (STAT3).